Heat-Damaged RBC Scan. (May 2015) - Tamm, Alexander; Decker, Martha; Hoskinson, Michael; Abele, Jonathan; Patel, Vimal
<x xml:space="preserve">Abstract</x> Abstract Intrahepatic splenosis results from autotransplantation of splenic tissue within the liver, usually after splenic trauma or splenectomy. We present a case of a 43-year-old male patient with an incidental liver lesion discovered on abdominal ultrasound. The diagnosis of intrahepatic splenosis was considered after CT and MRI before being definitively made with 99mTc-labeled heat-damaged RBC scintigraphy. The case report illustrates the imaging characteristics of this rare location of abdominal splenosis.